2018
DOI: 10.1021/acsnano.8b00962
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Driven Giant Spin Dynamics at Three-Dimensional Heteroepitaxial Interface in Ni0.5Zn0.5Fe2O4/BaTiO3-Pillar Nanocomposites

Abstract: Traditional magnetostrictive/piezoelectric laminated composites rely on the two-dimensional interface that transfers stress/strain to achieve the large magnetoelectric (ME) coupling, nevertheless, they suffer from the theoretical limitation of the strain effect and of the substrate clamping effect in real ME applications. In this work, 3D NZFO/BTO-pillar nanocomposite films were grown on SrTiO by template-assisted pulsed laser deposition, where BaTiO (BTO) nanopillars appeared in an array with distinct phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…[ 18 ] Meanwhile, a thermal‐driven magnetic damping change was also achieved in Ni 0.5 Zn 0.5 Fe 2 O 4 (NZFO)/Pb(Mg 2/3 Nb 1/3 )‐PbTiO 3 (PMN−PT) 3D nanostructures. [ 19 ] However, these works are suffered from the high‐operation voltage (>400 V), high energy consumption, and challenge‐to‐be‐integrated problems, limiting their potential applications in the future. [ 18,19 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] Meanwhile, a thermal‐driven magnetic damping change was also achieved in Ni 0.5 Zn 0.5 Fe 2 O 4 (NZFO)/Pb(Mg 2/3 Nb 1/3 )‐PbTiO 3 (PMN−PT) 3D nanostructures. [ 19 ] However, these works are suffered from the high‐operation voltage (>400 V), high energy consumption, and challenge‐to‐be‐integrated problems, limiting their potential applications in the future. [ 18,19 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] However, these works are suffered from the high‐operation voltage (>400 V), high energy consumption, and challenge‐to‐be‐integrated problems, limiting their potential applications in the future. [ 18,19 ]…”
Section: Introductionmentioning
confidence: 99%
“…12−16 Dong et al reported that the 3D Ni 0.5 Zn 0.5 Fe 2 O 4 /BaTiO 3pillar nanocomposite exhibits excellent magnetoelectric coupling at the interface, which they have attributed to effective strain transfer at the 3D interface. 13 While Xue et al have used magnetically frustrated NZFO as a prototype for Efield control of the two-magnon scattering (TMS) effect in NZFO/PMN-PT heterostructures, their study further revealed a large anisotropic spin-freezing temperature change of 160 K in the NZFO system. 14 Recently, Zhang et al have developed a tunable magnetoelectric inductor using symmetrical trilayers of Ga-doped NiZn ferrite, which can be tuned in a bidirectional way with a maximum inductance tunability of 571%.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years, Ni 0.5 Zn 0.5 Fe 2 O 4 (NZFO) nanoferrites and their nanocomposites have been investigated extensively for their advanced technological applications. Dong et al reported that the 3D Ni 0.5 Zn 0.5 Fe 2 O 4 /BaTiO 3 -pillar nanocomposite exhibits excellent magnetoelectric coupling at the interface, which they have attributed to effective strain transfer at the 3D interface . While Xue et al have used magnetically frustrated NZFO as a prototype for E-field control of the two-magnon scattering (TMS) effect in NZFO/PMN-PT heterostructures, their study further revealed a large anisotropic spin-freezing temperature change of 160 K in the NZFO system .…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of the laser-induced magnetization dynamics, , a huge progress saw the light of day regarding the theoretical and experimental study of ultrafast spin dynamics on both extended and molecular systems. Motivated by the ability of the spin to act as an information carrier, which, contrary to the electrical charge in conventional semiconductor based logic elements, can achieve higher information densities and data processing speeds at potentially lower energy consumption, many mechanisms and a large variety of systems have been proposed. Especially molecular systems have the potential to miniaturize the envisaged magnetic-logic elements, since they can accommodate Boolean logic processes, and already several logic operations have been proposed on the basis of realistic or even synthesized molecular systems. Additionally, the recent advances with respect to nanoscale on-chip integrated light sources , corroborate the importance of molecular magnets for use in nanospintronics devices. , …”
mentioning
confidence: 99%